2018
DOI: 10.3892/etm.2018.6914
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of clinical features with hs‑CRP in TRD patients

Abstract: Correlation of clinical features with hypersensitive C-reactive protein (hs-CRP) in patients with treatment-resistant depression (TRD) was investigated. The severity of disease in 103 TRD patients and 103 non-TRD patients was evaluated using the Hamilton Depression Scale (HAMD)-17. The levels of hs-CRP in both groups were detected via immunofluorescence. Clinical features and differences in hs-CRP before and after treatment in both groups were analyzed, and correlation of baseline hs-CRP level with clinical fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Based on the abovementioned inflammatory theory of depression, several studies investigated the association between CRP levels and antidepressant treatment [123]. A wide range of studies reported that elevated levels of CRP were associated with TRD patients [50,60,78,84,95,97]. Conversely, other studies showed that lower levels of CRP were associated with a better and faster response to SSRI treatment [63,98].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the abovementioned inflammatory theory of depression, several studies investigated the association between CRP levels and antidepressant treatment [123]. A wide range of studies reported that elevated levels of CRP were associated with TRD patients [50,60,78,84,95,97]. Conversely, other studies showed that lower levels of CRP were associated with a better and faster response to SSRI treatment [63,98].…”
Section: Discussionmentioning
confidence: 99%
“…In the TRD group, the disease course was longer, the onset was earlier, and the educational level was lower. The HAMD score (p = 0.031), anxiety/somatization factor score (p = 0.015), and sleep disorder (p = 0.029) of TRD patients were positively associated with hs-CRP level, while the onset age (p = 0.009) was negatively correlated with the hs-CRP level [84].…”
Section: Case-control Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Overall medical costs for TRD patients are almost twice or more than twice as high as those for nTRD patients (8,9). In terms of clinical symptoms, compared with nTRD patients, TRD patients had more severe depressive symptoms, cognitive impairment, anxiety and distress, longer onset period, and lower work productivity (7,(10)(11)(12). Therefore, it is necessary to explore the biomarkers of TRD, which in turn will facilitate the understanding of the differences in the pathogenesis of TRD and nTRD.…”
Section: Introductionmentioning
confidence: 99%